Benin : Assessment Letter for the World Bank. (Policy Papers; Policy Paper ;, 2010)
Technical Assistance (TA) is one of the IMF's core activities whose purpose is to help member countries improve the design and implementation of their macroeconomic policies. To ensure that the Fund's TA meets the needs of the membership, and is efficient and effective, the Executive Board established in 2002 the TA Evaluation Program. Under this program, announced to the Executive Board on a three-year rolling schedule, each year a number of evaluations are carried out. These consist of self-assessments by IMF departments providing TA plus independent assessments of donor-financed TA. Since 2003, more than two dozen TA evaluations were produced, covering all IMF TA departments plus the IMF's Regional Technical Assistance Centers (RTACs). Periodically the IMF staff submits to the Executive Board a review of the findings of the TA evaluation reports produced during the preceding period.